Antioxidant Activity of Jicama Roots (Bengkoang) in Several Harvesting Age Using DPPH Method (2,2-diphenyl-1-picrylhydrazyl. - Juni Annida Lintang; Herla Rusmarilin; Linda Masniary Lubis (Jurnal Rekayasa Pangan dan Pertanian, 2014)
Jicama or yam bean is Fabaceae Family which is potential as a source of antioxidants as it is rich in flavonoid and phytoestrogen. The research was performed in three stages. Stage I: Making of jicama flour with one factor (harvesting age (U): (3, 4, and 5 months). Stage II: Making of jicama methanolic extract with one factor (harvesting age (U): (3, 4, and 5 months). Stage III: Estimating the antioxidant activity of ether/water fractions of methanolic extract with two factors i.e: concentration (K): (10, 20, 40, 80, 160 ppm) and harvesting age (U): (3,4, and 5 months). The results showed that the harvesting age had highly significant effect on proximate composition of jicama flour and yield of methanolic extract. Moisture content, ash content, and fat content tended to decrease with increasing harvesting age. Meanwhile, crude fiber content tended to increase. The protein content of jicama flour and yield of methanolic extract were maximum at 4 month harvest and tended to decrease at 5 months. The interaction of concentration and harvesting age had highly significant effect on antioxidant activity. The antioxidant of ether fraction tended to increase, but the antioxidant of the water fraction tended to decrease with increasing the harvesting age. The antioxidant of jicama methanolic extract is categorized as a strong antioxidant because the IC50 ether/water fractions were less than 100 ppm. Keywords : Antioxidant, DPPH, ether fraction, water fraction.